The labour of subjectivity Foucault on biopolitics, economy, critique - Rossi, Andrea (Research Fellow) (Rowman & Littlefield International, 2016)
The book re-examines the genealogy of the politics of subjectivity that Foucault began to outline in his lectures at the College de France in the late 1970s and early 1980s. He explores Christian confession, raison d'etat, biopolitics and bioeconomy as the different technologies by which Western politics has attempted to produce, regulate and give form to the subjectivity of its subjects. Ultimately Rossi argues that Foucault's critical project can only be comprehended within the context of this historico-political trajectory, as an attempt to give the extant politics of the self a new horizon.